A phase 1, randomized, double-blind, placebo-controlled, dose escalation study to evaluate the safety, tolerability, pharmacokinetics and immunogenicity of SHR-1905, a long-acting anti-thymic stromal lymphopoietin antibody, in healthy subjects - Fei, Yue; Li, Na; Qian, Weilin; Fan, Yang; Shen, Yu; Wang, Quanren; McLendon, Kristi; Shen, Kai (Frontiers in Pharmacology, 2024)
Introduction: Thymic stromal lymphopoietin (TSLP) is integral to inducing innate and T helper 2 cell inflammation that leads to clinical symptoms of asthma. SHR-1905 is a humanized immunoglobulin G1 kappa monoclonal antibody that inhibits TSLP bioactivity, developed for the treatment of severe uncontrolled asthma. This phase 1, randomized, double-blind, placebo-controlled single ascending dose study assessed the safety, tolerability, pharmacokinetics (PK), and immunogenicity of subcutaneous SHR-1905 in healthy subjects. Methods: Five dose cohorts were planned (50, 100, 200, 400, and 600 mg) and subjects were randomized (8:2) in each cohort to receive SHR-1905 or placebo with a follow-up period up to Day 253. Results: The majority of treatment-emergent adverse events (TEAEs) were mild and the incidence of TEAEs was comparable between the SHR-1905 and the placebo groups. The maximum serum concentration was reached 7.0 to 17.6 days after injection. The serum concentration of SHR-1905 increased with increasing dose level, and SHR-1905 exposure exhibited in a slightly greater-than-dose-proportional manner from 50 to 600 mg. SHR-1905 had a prolonged serum half-life around 80 days supporting every 6-month dosing. In SHR-1905 treated subjects, 15% tested positive for anti-drug antibodies post-dose with no apparent effect on corresponding PK profiles or safety. Conclusion: SHR-1905 demonstrated a good safety and tolerability profile with a long half-life in healthy subjects after a single administration in the dose range of 50 to 600 mg. Clinical Trial Registration: ClinicalTrials.gov, NCT04800263